Influence of Temperature And Concentration of Ethanol on Properties of Borosilicate Glass Photonic Crystal Fiber Infiltrated by Water – Ethanol Mixture - Le Van, Hieu; Nguyen, Hue Thi; Ho Dinh, Quang; Cao Long, Van (Communications in Physics, 2018)
In this paper, we present a numerical simulation of the properties of a photonic crystal fiber (PCF) made of borosilicate glass infiltrated by the water-ethanol mixture. We examine the influence of temperature and ethanol concentration for the refractive index, dispersion properties, effective mode area and confinement loss of the fundamental mode by a Lumerical simulation method. We also calculate the fundamental mode of the fiber infiltrated with a water-ethanol mixture with the concentration range of ethanol from 0% to 100% in the temperature range from 10°C to boiling point of ethanol. The results show that all fibers infiltrated with water-ethanol mixture have flat dispersion characteristics in the infrared range above 1.32. The best flatness exists for pure ethanol. Furthermore, it is possible to shift the zero-dispersion wavelength and modify fundamental properties of PCFs by both temperature and concentration of ethanol. The results obtained are important because of that we not only use their reasonable parameters for the design and manufacture but also use them in nonlinear phenomena and nonlinear applications of fibers as supercontinuum generation.